Analysis of glass fiber reinforced with epoxy resin using FEM. (2021) - Kishore, Chandra; Jaiswal, Ritik; Bhatt, Vinayak; Jugran, Shivam; Rawat, Dipak; Verma, Deepak
Abstract: Application of GFRP has been increased from the past as they offer much enhanced properties. This development is the new spear head of the material technology due to its incomparable potential. Glass fibers are known to be as very versatile industrial material and they exhibit useful bulk as well as fiber properties whereas Epoxy resin has many industrial applications for a different range of special purposes. Reinforcing them together in different variation leads to a significant enhancement in their overall properties. This paper investigates the variation in the properties of GFRP with the variation in the fiber mass percentage. ASTM standard test specimen are utilized and test is carried out with the help of Ansys Academic software. The primary objective of this paper is to evaluate equivalent stress, strain and total deformation of the composite under same load.